Antibody profile following vaccination with thermostable (ND-I2) vaccine in village chicken that survived the Newcastle disease outbreak - Abubakar, Mustapha B.; Amshi, Kazabu; El-Yuguda, A. D.; Baba, S. S.; Gambo, H. I.; Geidam, Y. A.; Shettim, Y. M.; Zannah, Y. M.; Abu, Jalila; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The antibody profile of village chickens that recovered from clinical Newcastle disease infection were monitored following vaccination with thermostable (NDI2-HR) vaccine over a period of 5 weeks. The birds were grouped into two: vaccinated and non-vaccinated. Antibody profile was determined using haemagglutination inhibition (HI) test. Seromonitoring result revealed a significant (p<0.05) seroconversion with rise in Geometric antibody titer (GMT) values of antibody among the vaccinated birds that survived the outbreak, with peaked at week two following vaccination and declined subsequently in both study groups. No significant difference was observed in the antibody profile of vaccinated and non-vaccinated group which is an indication of low response to vaccination. Vaccination of surviving birds following ND outbreak may be of little value in development of immunity to the disease.